Performance of Mutual Funds Amidst COVID 19 - A Study on Selected Equity Diversified Categories in India - Naveen, Shaini; Mallikarjunappa, T. (Indian Journal of Research in Capital Markets, 2022)
The increasing assets under management (AUM) and the number of funds and schemes over the years have shown an exemplary performance of the mutual fund industry. It has gained popularity among investors for parking their surplus funds much safer than the stock market. This research paper investigated the performance evaluation of large, mid, small, and multi-cap categories from equity diversified funds using statistical parameters like standard deviation, beta, Sharpe ratio, Treynor's index, and Jensen's measure for risk-return analysis. The correlation analysis for the time series along with Nifty 100 TRI as the benchmark was analyzed. The pandemic effect was studied using a multiple regression model, and the results were tested with residual diagnostics. A total of 93 open-ended schemes were selected from the four categories and studied for a period of 4 years from April 2017 – March 2021 with the outbreak of the COVID - 19 in December 2019. The study analyzed the pre and post-pandemic effect on the performance using a dummy variable. The results showed average performance in the case of large, mid, and multi-cap funds, but small-cap funds outperformed the benchmark. The dummy coefficient showing the pandemic effect was positive and statistically significant for the fund categories selected for the study. The pandemic effect did not find average negative performance for the period, and the model was found to be the best fit through the robustness check. However, the fund categories, on the whole, showed a high correlation and were in tandem with the market.